Gender inequities and HIV prevalence and AIDS mortality: Findings from the United Nation countries - Khammarnia, Mohammad; Hatam, Nahid; Faraji, Mohammad Hossein (South East Asia Journal of Public Health, 2015)
In the last years, the prevalence Human immune deficiency virus (HIV) have increased worldwide, specifically in developing countries due to a number of causes. This study aimed was to determination the relationship between gender inequities, HIV prevalence and AIDS mortality in the United Nation countries. A cross-sectional retrospective study was conducted in 2013 and all the countries (187 countries) which were included in the WHO and UN Annual Reports (2012) were considered. One hundred and forty four countries were selected which had the completed indices of gender inequities (GI), HIV morbidity and AIDS mortality in the reports. The findings showed that there was direct association between the gender inequities, HIV prevalence and AIDS mortality (p=0.001). The level of GI among low-income countries (0.41) was higher than others groups, and approximately twice as much as that of high-income countries (0.19). It was noted that GI had a significant association with the AIDS mortality in the high-income countries (p=0.031). Moreover, in the upper middle income countries, the both indices (HIV morbidity and AIDS mortality) had significant positive association with the GI (p<0.05). However, the highest level of significant relationship was between being HIV/AIDS mortality and morbidity with the GI in low income countries (p<0.00l). It was observed that GI led to HIV/AIDS mortality and morbidity in all countries specifically in developing countries. Specific strategies should be implemented to decrease the gender inequities by the provision of women education and empowermen and improvement of socio-economic status to reduce HIV/AIDS morbidity and mortality. South East Asia Journal of Public Health Vol.4(2) 2014: 51-54